Revilazitation of the tettye park: Presentation of one of the main elments of the open space renewal project of 11,5 hectares realized in a historical district and nature conservation area - Mohácsi, Sándor (4D Journal of Landscape Architecture and Garden Art, 2011)
According to a certain interpretation, the Tettye Park is the green wedge of the Mecsek’s natural landscape which reaches all the way to the bordér of the medieval town. This is a unique PLACE, owing its values since the Middle Ages most of all to its excellent landscape characteristics.This paper is organically linked to the article published in the 16. edition of 4D in 2009 with the title ‘Renewal ofthe district Pécs-Tettye’. Then, we offered a presentation of the objec- tives and achievements of the design contest fór the district area. This time we are aiming, simultaneously to the rhythm of their realization, at giving somé professional publicity to the indi- vidual elements of the project. This intention is justified by the fact that many short, médium and long term professional conclusions can be drawn from this project, which, even in an international comparison seems to be of an outstanding quality. However, before getting down to the long analytical work, we need to present the achieved result and the road which has led us there.
Keywords: revitalization; Tettye park; open space planning; public park